Cônicas: explorando distâncias - Santos, Érick dos (2023)
In this work we extend the study of conics, as geometric places, to a larger set of subsets of a plane, exploring the metric concepts that give rise to conics. In this sense, we list the geometric places obtained from equidistance, constant sum of distances and constant difference of distances in relation to two of the following objects: points, lines and circumferences. The result of this is an abundance of images where conics continue to be protagonists.